Case Report: Occupational bullous dermatosis: first report of skin lesions induced by PVC welding fume in a manufacturing worker - Stufano, Angela; Lovreglio, Piero; Cazzato, Gerardo; Danza, Paolo; Ravallese, Riccardo; Cassano, Nicoletta; Vena, Gino Antonio; Ambrogio, Francesca; Tirone, Benedetta; Foti, Caterina (Frontiers in Immunology, 2025)
PurposeBullous dermatoses encompass a group of disorders marked by blister formation on the skin and/or mucosa with diverse etiologies. This case report aims to describe a rare occupationally induced bullous dermatosis in a worker exposed to polyvinyl chloride (PVC) welding fumes, and to highlight the need for improved protective measures in industrial environments.MethodsA 48-year-old male employed in a PVC manufacturing plant developed recurrent bullous skin lesions on the hands, face, and neck after operating a PVC film-welding machine without personal protective equipment. Clinical evaluation was supported by histopathology, direct and indirect immunofluorescence, serologic testing (ELISA for anti-desmoglein-1, anti-desmoglein-3, BP230, and BP180), and a porphyrin screen. Patch tests and autoimmunity screening were also performed.ResultsDirect immunofluorescence revealed linear C3 and IgG deposits along the basement membrane zone, consistent with a bullous pemphigoid-like pattern, while other autoimmunity markers were negative. Complete remission of lesions occurred after cessation of exposure and job reassignment, without the need for ongoing pharmacologic treatment. A clear “stop-restart” relationship between exposure and symptoms supported a causal association.ConclusionThis report describes the first documented case of bullous dermatosis triggered by occupational exposure to PVC welding fumes. The findings emphasize the relevance of occupational assessment in unusual dermatologic presentations and support the implementation of adequate protective measures and exposure monitoring in high-risk settings.